Which plasticizer is suitable for films based on babassu starch isolated by different methods?. (April 2019) - Maniglia, Bianca C.; Tessaro, Larissa; Ramos, Ana Paula; Tapia-Blácido, Delia R.
Abstract: This work aimed to determine which plasticizer is suitable for films based on babassu starch isolated by steeping in water (WS), acid steeping (AS), or alkaline steeping (KS) with a view to obtaining less hydrophilic films with good mechanical properties. We used glycerol, sorbitol, glucose, or urea as plasticizers and determined the resulting film physical and functional properties. Plasticizer type did not affect film color or antioxidant activity, but it impacted film opacity and physical and functional properties. As verified by FTIR and SEM, the babassu starches presented different chemical composition and structure, so plasticizers affected AS, WS, and KS starch film properties differently. Glycerol and urea yielded more hydrophilic, more permeable to water vapor, less opaque, less mechanically resistant, and less crystalline AS and KS starch films. Meanwhile, WS starch films showed this behavior when sorbitol or glucose was used as plasticizer. Glucose provided films that were less permeable to water vapor regardless of starch type. With respect to application in food packaging, sorbitol was the most suitable plasticizer for AS and KS starch films, whereas glycerol was the most adequate plasticizer for WS starch film. Graphical abstract: Highlights: Glycerol, sorbitol, urea, and glucose were evaluated as plasticizers for babassu starch films. Glycerol and urea are more effective plasticizers for the AS (acid steeping) and KS (alkaline steeping) starch films. Sorbitol and glucose were more effective plasticizers for the WS (water steeping) starch film. Glucose yielded babassu starch film with lower water vapor permeability. The most suitable plasticizer for AS and KS starch films was sorbitol, and for WS starch film was glycerol.